A new locality and reassessment of the type series of the Machu Picchu Andean lizard Proctoporus machupicchu Mamani, Goicoechea and Chaparro, 2015 (Squamata: Gymnophthalmidae) - Diaz, M. Isabel (2019)
Proctoporus machupicchu is a semi-fossorial lizard, which was discovered in two locations in the Historic Sanctuary of Machu Picchu (SHMP), Urubamba province, Cusco, Peru. The type series consists of two females and a male, however, the male paratype does not possess femoral pores which is incongruous with the males mentioned in the literature. In this paper, we report a new location outside the SHMP and re-examine the type series. Internally, the male paratype has no male vestiges (testicles and seminiferous ducts), so we conclude that there was an error in sexing. In addition, we report a new locality based on a juvenile male collected in the San Luis Private Conservation Area (ACP San Luis) of La Convención province. This new record increases the range of distribution of the species by 20.9km to the northeast and its altitudinal range from 2760 – 2800 to 2760 – 2966 m of altitude.